Brain metastasis in colorectal cancer presenting as refractory hypertension - Syed Moin Hassan; Ateeq Mubarik; Salman Muddassir; Furqan Haq (Greater Baltimore Medical Center, 2018)
Background: Brain metastasis (BM) from colorectal cancer (CRC) is rare with the incidence ranging from 0.6% to 3.2%. There is also an increased incidence of BM with rectal primaries and is consistent with this patient's presentation. Overall, there is scarce literature on the symptoms of patients who present with CRC BMs. Objectives: We present a case of brain metastasis in colorectal cancer presenting with hypertensive urgency and severe headache. Methods and results: This case highlights that neurological deficits are not necessary for BMs in patients with CRC and summarizes and reviews the associated literature regarding BM in CRC. A 57-year-old female with a past medical history of recently diagnosed stage IV moderately differentiated distal rectal adenocarcinoma with liver and lung metastasis was admitted with the primary complaint of hypertensive urgency, severe headache, intractable nausea and vomiting, and diarrhea. Magnetic resonance imaging brain showed a left cerebellar lesion measuring 3.6 × 3.2 × 2.9 cm, ipsilateral transtentorial herniation, and obliteration of the fourth ventricle. The patient was started on steroids and transferred for an urgent neurosurgical intervention to a tertiary care center. Conclusions: Even though BMs are rare in CRC, clinicians should have a high index of suspicion with complaints like hypertensive urgency, headache, nausea, vomiting, vertigo, and blurring of vision triggering imaging studies to rule out BM. The approach to BM has become increasingly individualized as surgical and radiosurgical therapies have continued to evolve Abbreviations: CRC: Colorectal cancer; BM: Brain metastasis; FOLFOX: Folinic acid, fluorouracil and oxaliplatin; CT: Computed tomography; IV: Intravenous; PO: By mouth; BAER: Brain auditory evoked response hearing testing; SSEP's: Somatosensory evoked potentials; BMFI: Brain metastasis free interval; WBRT: Whole-brain radiation therapy; SRS: Stereotactic radiosurgery.